PELATIHAN DAN SOSIALISASI APLIKASI E-LEARNING EDMODO PADA MASA PANDEMI COVID-19 DI SMPN 1 NDONA - Desta Gloria Siahaan; Lukas Pardosi (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2022)
Utilization of information and communication technology media has penetrated into all areas of life. One of the uses of information and communication technology media in the field of education is e-learning. E-learning (electronic learning) is a learning process that utilizes information technology in this case utilizing online media such as the internet as a method of delivery, interaction and facilitation. The use of e-learning platforms can make it easier for teachers and students in the learning process. The objectives of this activity are: First, to provide concepts and to disseminate the use of Edmodo for the learning process. Second, providing knowledge about how to use and apply the features contained in the Edmodo platform to facilitate the learning process. The targets for this community service are teachers at SMP Negeri 1 Ndona, Ende. This community service is expected to be able to provide additional skills for teachers how to use the e-learning platform (edmodo) for free to support conventional learning during this covid-19 pandemic.